2018
DOI: 10.1371/journal.pone.0198918
|View full text |Cite
|
Sign up to set email alerts
|

Gender and age-specific aspects of awareness and knowledge in basic life support

Abstract: BackgroundThe ‘chain of survival’—including early call for help, early cardiopulmonary resuscitation (CPR) and early defibrillation—represents the most beneficial approach for favourable patient outcome after out-of-hospital cardiac arrest (OHCA). Despite increasing numbers of publicly accessible automated external defibrillators (AED) and interventions to increase public awareness for basic life support (BLS), the number of their use in real-life emergency situations remains low.MethodsIn this prospective pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
2
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 18 publications
5
44
2
8
Order By: Relevance
“…With respect to the sex of rescuers, researchers in Austria found that women were less willing to provide bystander CPR or to apply an automated external defibrillator to a person who had collapsed from cardiac arrest. 21 We propose that a potential factor that might mitigate some of this disparity is to encourage, empower and educate more women to provide bystander CPR.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to the sex of rescuers, researchers in Austria found that women were less willing to provide bystander CPR or to apply an automated external defibrillator to a person who had collapsed from cardiac arrest. 21 We propose that a potential factor that might mitigate some of this disparity is to encourage, empower and educate more women to provide bystander CPR.…”
Section: Discussionmentioning
confidence: 99%
“…This highlights an ongoing need for CPR refresher training. 17 18 People in non-medical-related occupations attach less importance to CPR, which could be attributable to the fact that CPR training is not recommended as a compulsory curriculum, except in medical schools in China. Moreover, previous training experience does help improve their attitudes.…”
Section: Discussionmentioning
confidence: 99%
“…However, even in the most advanced emergency systems, the emergency personnel needs a medium time of 5-8 min to arrive at the emergency site [ 2 ]. Therefore, it is crucial that a bystander—that is, a person noticing the cardiac arrest—starts CPR [ 3 , 4 ]. In the majority of cases, the bystander will be a medical layperson [ 5 ].…”
Section: Introductionmentioning
confidence: 99%